Analysis of the Use of Artificial Intelligence in the Accounting Profession - Febrianti, Arizqi; Rudianti, Walid; Purbandary, Yenny; Ainiyah, Ghonimah Zumroatun; Permatasari, Kartika Dewi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the use of Artificial Intelligence (AI) in the accounting profession in Banjarnegara Regency, Central Java. Using a qualitative approach, the research focuses on accounting students' perceptions of AI, the challenges and opportunities of integrating AI into accounting, and its impact on the performance of accounting practitioners. Data collection was conducted through in-depth interviews with three accounting students and two accounting practitioners, supplemented by documentation. The findings of the study indicate that: (1) Accounting students have a positive perception of the use of AI in learning and completing accounting tasks; (2) The integration of AI in accounting presents opportunities for work efficiency while also posing challenges in adapting competencies; (3) The utilization of AI enhances the performance and effectiveness of accounting practitioners, although it introduces risks of dependency and data security. This research contributes empirically to the transformation of the accountant's  role  in  the  digital  era  and  implies  the  need  for  the  development  of  accounting education  curricula  that  integrate  AI  technology,  as  well  as  the  enhancement  of  digital competencies for accounting practitioners.